Multi-body dynamics modeling and test of an articulated steering half-track tractor - Zhou, Baocheng; Chen, Shiyu; Hu, Jianing; You, Yong; Wang, Decheng; Zhang, Qing (International Journal of Agricultural and Biological Engineering, 2024)
With the benefits of small turning radius and high trafficability, the articulated steering half-track tractor had been widely utilized in orchard and small spaced farmland. To study the dynamic performance of the articulated steering half-track tractor and provide a model basis for studying the path tracking control, an accurate multi-body dynamic model of the tractor was required. In this study, the crucial parameters in the dynamic model construction of the tractor were investigated. Firstly, the topology model of the components of the half-track tractor was built by RecurDyn, in which the movement subs and driver functions were given. Secondly, considering the difference of dynamic characteristic of the articulated steering tractor with respect to different pavement hardnesses, the soft and hard pavement models were constructed by employing the harmonic superposition method. Finally, the simulations of the half-track tractor under straight-line and swerve had been conducted on the two types of pavements, and the simulation results were compared with the experimental and theoretical results. The results indicated that the average speed error of the dynamic model on hard pavement and farmland soft pavement were 2.7% and 2.1% compared with the real tractor tests. At the same time, the straight-line driving offset errors of the dynamic model on the two pavements were 1.6% and 3.8% for the front wheels and the rear wheels offset errors were 3.9% and 2.4%, respectively. Furthermore, the turning radius error under front wheel steering was 8.2% and the error under articulated steering was 5.3%. It is proved that the established dynamic model had high accuracy, which provides an efficient approach to analyze the dynamic features of the half-track tractor.Keywords: articulated steering, half-track tractor, multi-body dynamics, model verification, real tractor testDOI: 10.25165/j.ijabe.20231606.8165Citation: Zhou B C, Chen S Y, Hu J N, You Y, Wang D C, Zhang Q. Multi-body dynamics modeling and test of an articulated steering half-track tractor. Int J Agric & Biol Eng, 2023; 16(6): 124–133.